Educators continuing education: reflections on the conceptions expressed by municipal teachers from Soledade, RS (Research, Society and Development, 2017)
This article has as main goal to analyze the municipal teachers’ conceptions from Soledade, RS regarding the continuing education. To this purpose, Municipal Department of Education, Culture and Sport performed an exploratory research type in the year 2013. Constituted as a case study, the research aforementioned aimed at subsidizing the construction of public policies for the continuing education. Qualitative data were gathered from the municipal teachers, by means of a standardized questionnaire and descriptive assessments, in the context of the system continuing education meetings and municipal step of the 2nd National Conference on Education. The content analysis performed on the data gathered, subsidized in authors such as Paulo Freire and Elli Benincá, allowed to understand that, according to the municipal teachers’ general understanding, continuing education is synonymous of procedural actions that must be effected in schools and within the weekly work shift.  Moreover, the teachers made explicit a preference for continuing education by means of pedagogical workshops, in order to fulfill the issues regarding the methodological-didactic dimension. In this sense, another point that arises with strength in the speeches regards to the centrality of practice, to the detriment of the pedagogical theory: the "know-how-to-do" is the main goal that must guide the continuing education activities. In conclusion, the construction of continuing education as a critical reflection on practice, in order to problematize the educational phenomenon in its multiple determinations, poses itself as a central challenge to the Municipal System of Education in Soledade, RS.